Laboratory training in the retrosigmoid approach using cadaveric silicone injected cow brain - BAYRİ, YAŞAR (INFORMA HEALTHCARE, 2013)
Background. A neurosurgical laboratory training model is designed for trainees in microneurosurgery to learn to handle surgical microscopes and microneurosurgical instruments. The silicone injection of a fresh cadaveric cow cranium is an alternative to using a cadaveric human brain for becoming familiar with the cerebellopontine angle (CPA) via the retrosigmoid approach. To report an improved method for training in the CPA via the retrosigmoid approach, using a fresh cadaveric cow cranium injected with silicone. Methods. The material consists of a cadaveric cow brain injected with silicone. Preparation consists of irrigation of the major vessels followed by injection of silicone, coloured either red or blue. Results. A three-step approach was designed to simulate microneurosurgical dissection along with the cerebellopontine angle and to dissect cranial nerves emerging from the brain stem. Conclusion. This laboratory training model is useful in allowing trainees to gain experience with the use of an operating microscope and familiarity with the CPA via the retrosigmoid approach. The aim of this study was to develop a novel model and to adapt it to create a life-like neurosurgical training system.
Keywords: cerebellopontine angle; cranial nerve; microneurosurgery; neurosurgical training; MODEL; SURGERY